A computational and experimental study of thermal energy separation by swirl. (September 2018) - Kobiela, B.; Younis, B.A.; Weigand, B.; Neumann, O.
Highlights: Analysis of the heat-transfer mechanism underlying thermal energy separation by swirl. Formulation of an explicit, algebraic model for the turbulent heat fluxes that correctly represents the effects of the gradients of mean velocity and pressure on these fluxes. The acquisition of experimental measurements of compressible flow in a swirl chamber suitable for model validation. Three-dimensional computations utilizing the new model showing distinct improvements over conventional turbulence closures. Abstract: When compressed air is introduced into a tube in such a way as to generate a strong axial vortex, an interesting phenomenon is observed wherein the fluid temperature at the vortex core drops below the inlet value, while in the outer part of the vortex, the temperature is higher than at inlet. The most familiar manifestation of this phenomenon is known as the Ranque-Hilsch effect, and several alternative explanations for it have been proposed. In this study, we present an analysis of the heat transfer mechanism underlying this phenomenon, based on consideration of the exact equation governing the conservation of the turbulent heat fluxes. The outcome is a model that explicitly accounts for the dependence of the heat fluxes on the mean rates of strain, and on the gradients of mean pressure. These dependencies, which are absent from conventional closures, are required by the exact equation. To verify the model, an experimental investigation of flow in a swirl chamber was conducted, and the measurements were used to check the model's performance as obtained by three-dimensional numerical simulations. Comparisons between predictions and measurements demonstrate that the new model yields predictions that are distinctly better than those obtained using conventional closures.